STRATEGI ADAPTASI NELAYAN TRADISIONAL DALAM MEMENUHI KEBUTUHAN KELUARGA DI KELURAHAN GURAPING KECAMATAN OBA UTARA KOTA TIDORE KEPULAUAN PROVINSI MALUKU UTARA - A. Ahmad, Muhammad Afandi; Wahab, Abdul (Universitas Islam Negeri Alauddin Makassar, 2019)
This research was conducted to determine the form of adaptation strategy of traditional fishermen in meeting the needs of families in the Guraping area and to find out how the inhibiting factors and supporting factors of fishermen in meeting family needs in Guraping Village, North Oba District, Tidore Islands City. The purpose of this study was to determine the strategy of traditional fishermen in meeting the needs of families and to determine the inhibiting factors and supporting factors of traditional fishermen in meeting the needs of families in Guraping Village, North Oba Subdistrict, Tidore Islands City. This type of research is a qualitative descriptive type. Data collection is done by conducting observations, interviews and documentation. This research approach uses the sociology approach. Data processing and analysis techniques go through three stages: data reduction, data presentation and conclusion drawing.The results showed that the strategies of traditional fishermen in meeting family needs are: 1) Strategies undertaken by traditional fishermen in meeting the needs of families besides working as fishermen, fishermen in Kelurahan Guraping also work as farmers, construction workers, the role of family members or by pressing expenses to meet the needs of his family. 2) The inhibiting factors of traditional fishermen in meeting family needs are: Climate change, marketing of catches that are still weak, the range of traditional fishermen sailing, and types of fishing gear. Supporting factors of traditional fishermen in meeting family needs are: (Without Fuel) Traditional fishermen in the Kelurahan of the sea do not need to use fuel so the money that was used to be used for fuel is diverted to help meet family needs, increasing fishermen's income.